hsa-mir-483-3p modulates delayed breast cancer recurrence - Ok-Hyeon Kim; Tae Jin Jeon; Hana Kang; Eun Seo Chang; Soon Auck Hong; Min Kyoon Kim; Hyun Jung Lee (Scientific Reports)
Abstract Patients with estrogen receptor-positive breast cancer undergoing continuous adjuvant hormone therapy often experience delayed recurrence with tamoxifen use, potentially causing adverse effects. However, the lack of biomarkers hampers patient selection for extended endocrine therapy. This study aimed to elucidate the molecular mechanisms underlying delayed recurrence and identify biomarkers. When miRNA expression was assessed in luminal breast cancer tissues with and without delayed recurrence using NanoString, a significant increase in the expression of miR483-3p was observed in samples from patients with delayed recurrence compared with those without. miR483-3p expression was elevated in tamoxifen resistant (TAMR) EFM19 cells than in non-resistant EFM19 cells. Notably, genes associated with cancer metastasis (AMOTL2, ANKRD1, CTGF, and VEGF) were upregulated in TAMR EFM19 cells, although cell motility and proliferation were reduced. Transfection of miR483-3p mimics into both non-resistant EFM19 and MCF7 cells resulted in increased expression of cancer metastasis-related genes, but decreased proliferation and migration. Given that miR483-3p can bind to the 3’UTR region of O-GlcNAc transferase (OGT) and potentially affect its protein expression, we examined OGT protein levels and found that transfection with miR483-3p mimics selectively reduced OGT expression. Overall, breast cancer cells subjected to long-term hormone therapy displayed elevated miR483-3p expression, reducing motility and dormancy induction via decreased OGT expression. These findings suggest that miR483-3p is a potential biomarker for long-term endocrine therapy.